Tubular and mucinous breast cancer: results of a cohort of 917 patients. Issue 1 (February 2019) - Roux, Pauline; Knight, Sophie; Cohen, Monique; Classe, Jean Marc; Mazouni, Chafika; Chauvet, Marie-Pierre; Reyal, Fabien; Colombo, Pierre-Emmanuel; Jouve, Eva; Chopin, Nicolas; Daraï, Emile; Coutant, Charles; et al.
Objectives: To analyze axillary lymph node involvement (ALNI) rate and survival for mucinous (MC) and tubular (TC) breast carcinomas considered being of very good prognosis and for which an axillary surgical exploration could be questioned. Methods: Our multicentric cohort consisted of 21, 135 patients with clinically node-negative invasive breast cancer, without neoadjuvant therapy, between 1999 and 2013 in 10 French centers. ALNI rate and survival were analyzed according to patient and tumor characteristics. Results: Our cohort consisted of 672 TC and 245 MC. Patients were older and tumor size greater for MC and pathologic factors were more pejorative. The rate of mastectomies and adjuvant chemotherapy was higher in the MC group. Axillary lymph node status was determined by SLNB alone in 71.2% of patients. ALNI rates were 17.9% and 18% for TC and MC, respectively. ALNI rate was lesser for MC (OR 0.503, p = 0.024) and greater in case of lympho-vascular invasion (OR 5.0, p < 0.0001) and for tumors >10 mm (OR 2.17, p = 0.042). Median follow-up was 58 months. The 5- and 7-year overall survival rates were 97.1% and 95% for TC, respectively; 92.3% and 91.2% for MC ( p = 0.043); 5- and 7-year disease-free survival rates were 97.9% and 97.2% versus 95.2 and 93.6% ( p = 0.041). Lympho-vascular invasion was the only predictive factor for overall survival (hazard ratio [HR] = 2.70)' grade 2 (HR = 10) and HR-negative (HR = 4.9) were the two predictive factors for disease-free survival. Conclusion: This study confirms the need for an axillary exploration for these tumors even for a tumor size <10 mm and a favorable prognosis.